The effects of the installation of the automatic lane barrier (alb) implementation on the IIUM community - Abdul Kadir, Hasnah; Abdul Rahman, Mahfuzah; Wok, Saodah (University College Islam Melaka, 2017)
To protect the campus community, security and safety remain a top priority for the university authority. In the case of the International Islamic University Malaysia (IIUM), the university decided to control traffic at all the entrances by installing the Automatic Lane Barrier (ALB). Hence, this study tries to figure out the effects of installation of ALB towards the IIUM community. The objectives of the study are: (1) to explore the sources of information obtained about ALB, (2) to determine the level of perceived usefulness (PU), perceived ease of use (PE), attitude and behaviour, (3) to analyse the relationship among selected variables on the ALB system, and (4) to test the mediating effect of attitude on behaviour. The Technology Acceptance Model (TAM) and the quantitative research design with self-administered questionnaires were used in the study. The questionnaires were distributed to 267 respondents. Results show that the respondents received information about the ALB mostly through IIUM website. The respondents think that ALB is useful but difficult to use. Overall, the respondents are not satisfied with the implementation and they had negative experiences with the ALB. In addition, the results indicate that there are positive relationships among the variables. After the installation of the ALB, the university received unsatisfactory responses from users.